Estimation of Pattern of Skull Fractures in Homicidal Deaths: An Autopsy Based Cross Sectional Study Conducted in a Tertiary Care Hospital (Indian Journal of Forensic Medicine & Toxicology, 2024)
The head is the most vital part of the body among various organs as the injury to the head will result in fataloutcomes compared to injuries sustained to other parts of the body. There has been an increased global incidence of head injuries in case of homicidal deaths. The present study aims to estimate the various patterns of the skull fractures in case of homicidal deaths and also the nature of injury causing such skull fractures in homicidal deaths.The present cross-sectional study revealed that out of 4036 autopsies, there were 74 cases of homicidal deaths with 67 male and 7 female cases. The skull fracture was noticed in 54 cases out of these 74 cases. The maximum number of homicidal deaths were found to be in the age group of 21 to 40 years. Among the different types of skull fractures, the isolated cut fracture contributed to 46.30% of cases followed by isolated fissured fractures and then by the combination of other types of skull fractures. The nature of injury causing skull fractures was blunt force in 51.8% of the cases then by sharp force injuries and then by the combination of these two. To bring down the incidence of homicidal deaths among the younger individuals, strict enforcements of law may be ensued on possession of blunt and sharp force weapons which are used for the brutal attacks.
Keywords: Homicidal deaths, Skull fractures, Blunt force.